RESEARCH IS A DAILY ACTIVITY AN UNDERSTANDING NEEDED TO ATTRACT THE ATTENTION OF PROSPECTIVE RESEARCHERS - Larasdiputra, Gde Deny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
Problems are something that will always arise in life. A problem solver is certainly the most sought after when a complex problem occurs, the cause is found, and even how to solve it. In situations like this,